Catalogue Æsthetics: Database In and As Music - Koutsomichalis, Marinos (My University, 2016)
The technological breakthroughs of the previous century caused a series of profound cultural shifts, which led to the digitalization of developed societies. Accordingly, the listening paradigm of the 21st century is no longer that of being passively exposed to music. Instead, contemporary audiences are typically expected to dynamically traverse collections of (big) data and, synthesize, rather than just access, musical content, employing several overlapping interfaces. In a similar fashion, the compositional schemata of the past have been shifted to account for the predominant symbolic form of our times, i.e. the Database. In that vein, several approaches to database (driven) music are scrutinized in this chapter, both in historical retrospective, as well as with respect to contemporary compositional practices.